Considerations on optimizing the patient experience during assisted reproductive technology treatment: a qualitative analysis - Li, Angela; Scalise, Ariel L.; Mayette, Emma; McGeorge, Nicolette; James, Kaitlyn; Mahalingaiah, Shruthi (F&S Reports (Online), 2025)
To study the structural and human factors that negatively and positively influence the patient experience during assisted reproductive technology (ART) treatment. Qualitative study involving 15 patients who had previously undergone ART, interviewed between August and October 2022. Consented participants underwent semistructured interviews. Transcripts were coded through the constant comparative method, and reflexive thematic analysis was performed to identify predominant themes. Individuals who underwent ART between January 2017 and April 2022. Assisted reproductive technology with transfer of at least one embryo. Factors positively and negatively influencing the patient experience. Themes identified from factors that negatively influenced care were the high burden and complexity of financing fertility treatment, unsatisfactory provider-patient communication, self-administration of injectable medications, and the complex and unpredictable nature of fertility treatment. Themes in factors that positively influenced care were positive provider rapport and collaborative decision making, social support networks, and alternative health therapies including acupuncture. Patients faced challenges with treatment financing, poor provider communication, and self-administration of injectable medications. However, positive provider relationships, social support, and complementary therapies such as acupuncture were identified as helpful factors.